Leia esta dissertação: descrição e análise de imperativos na interface sintaxe, semântica e pragmática - Masetto Nicolai, Yan (Universidade Federal de São Carlos, 2019)
The present work aims to treat through the syntactic-semantic-pragmatic interface of the imperative phenomenon in Brazilian Portuguese. For this to be possible, we will present and discuss some theories that have already worked and proposed some hypotheses. Through the field of generative syntax, we will bring Han (2000) together with the argument that imperatives have, at the top of the hierarchy of syntactic structure, an abstract operator [IMP] that determines both its force (directive), through a [directive] and the notion of unrealized action given by [irrealis], both abstract operators that are part of [IMP]. Also in the syntactic field, we will present the behavior of the imperatives when used in conjunction with the modifying adverbs, as treated by Tescari Neto (2008). In addition to the syntax, we will show that there is only one form, canonical, as given by grammars (CUNHA & CINTRA, 1985; ALMEIDA, 1995; BECHARA, 2009), but there are also imperative phrases: ‘Trata de’, ‘Deixa de’, ‘Para de’, ‘Pode’, ‘Nem pensa em’ e ‘Nem me vem com (essa de)’. From the formal Semantic perspective, specifically from the studies of intensionality, the work will deal with aspects already discussed by Portner (2004), with his Theory of Properties; Condoradvi & Lauer (2012), with its Theory of Performativity; and Kaufmann (2014), with his Modal Theory. After this incursion, we will present our own hypothesis: imperatives are, semantically, anchors of reality, as Kratzer (2015) argues, but they are indeed anchors of time, not of possible worlds, like modal verbs. In the semantic field, after presentation of the formalization of imperatives, From the pragmatic perspective, we will point out that the imperatives are sentences that, through the directive Speaking Act (OLIVEIRA, 1996), engage their listeners (or addressee - Ad). Let us proposing two principles to understand them. In the end, we will connect all the aspects brought within the three fields, discussing the relevant parts, the flaws and the ways of adapting them to our theoretical interface proposal. We will have a brief look and discuss two forms that are used in conjunction with them: imperative-like conditions (ILUs) and imperative-like ultimatums (ILUs), as discussed by Jary & Kissine (2014).
Read this dissertation: description and analysis of imperatives on the interface syntax, semantics and pragmatics
Keywords: Imperativos; Âncora de realidade; Engajamento de Ad; Interface; Imperatives; Reality anchors; Ad’s at-issuing; Interface; LINGUISTICA, LETRAS E ARTES::LINGUISTICA